Chemical Constitutents from Ajwain Seeds (Trachyspermum ammi) and Inhibitory Activity of Thymol, Lupeol and Fatty Acids on Barnyardgrass and Radish Seeds - CHUNG, ILL-MIN; DANG KHANH, TRAN; LEE, OH-KYU; AHMAD, ATEEQUE (Asian Journal of Chemistry, 2010)
The volatile oil of ajwain seeds (Trachyspermum ammi) was examined by gas chromatography and the major component thymol (1, 53.8%) was identified by spectroscopic studies and separated from volatile oil. After hydro distillation of the volatile oil of seeds have yielded several compounds lupeol (2), linoleic acid (3), stearic acid (4), eicosanoic acid (5), β-sitosterol-3-O-β-D-glucoside (6) from hexane : ethyl acetate: methanol extract. The structures of these compounds were elucidated with 500 MHz nuclear magnetic resonance, using 1D and 2D spectral methods, aided by electron ionization mass spectrometry (EI-MS), fast atom bombardment mass spectrometry (FAB-MS), infrared and compared with reported values and authentic samples. Regarding isolation of compounds from ajwain seeds, this is the first chemical investigation report. To the best of our knowledge, lupeol, linoleic acid, stearic acid, eicosanoic acid and β-sitosterol-3-O-β-Dglucoside were identified for the first time in ajwain seeds. In biological activity tests using these identified compounds thymol showed potent inhibitory activity against barnyardgrass (Echinochloa crus-galli) and radish seeds (Raphanus sativus) and was completely suppressed the germination and growth of shoot and root length. Lupeol exhibited also showed slightly inhibitory effect about 15 to 33% at concentration of 500 ppm to both barnyardgrass and radish seeds. The linoleic acid, stearic acid and eicosanoic acid did not show any strong inhibition effects against barnyardgrass.